Introduction: Breaking the Cycle of Mass Atrocities: Criminological and Socio-Legal Approaches to International Criminal Law. - Aksenova, Marina (Bloomsbury, 2020)
It is evident from the on-going debates on whether state policy is an element of crimes against humanity that this category of core international crimes still struggles with establishing its own identity. Originally conceived at Nuremberg as an extension of war crimes, it grew into an independent and ambitious legal category, which seeks to address gross human rights abuses committed on a massive scale in peace- and wartime alike. At the same time, this group of offences breeds a lot of ambiguity because of its over reliance on customary international law. With all the fluidity engendered by the weak legal foundation, where to find justification for international prosecution of crimes against humanity? This paper invokes criminologically related work of Emile Durkheim to support the claim that moral legitimacy of crimes against humanity as a group of offences flows from the feelings collectively shared by individuals across state borders. Repulsion towards certain acts is ingrained in the consciousness of people worldwide.
Keywords: Solidarity; Crimes against humanity; Durkheim; Global consciousness; Legal foundation; ODS 16 - Paz, justicia e instituciones sólidas